90 vs 50-Watt Radiofrequency Applications for Pulmonary Vein Isolation: Experimental and Clinical Findings. (1st April 2022) - Bortone, Agustín; Albenque, Jean-Paul; Ramirez, F. Daniel; Haïssaguerre, Michel; Combes, Stéphane; Constantin, Marion; Laborie, Guillaume; Brault-Noble, Guillaume; Marijon, Éloi; Jaïs, Pierre; Pambrun, Thomas
Abstract : Background: Fifty-watt radiofrequency applications have proven to be safe and efficient for pulmonary vein isolation (PVI). However, as PV reconnection still occurs and ablation catheter instability significantly contributes to suboptimal lesion formation, a new ablation catheter capable of delivering 90 W for 4 seconds only has been developed with the aim of improving PVI outcomes. In this setting, we sought to determine whether 90 W applications create transmural lesions without collateral damage experimentally and whether they can safely improve PVI procedures clinically compared with 50 W settings. Methods: Experimentally, individual lesions were created in vivo in the right atrium of 6 swine with 90 W-4 seconds applications using the SmartTouch-SF catheter in a power-controlled mode (3 animals) or the QDOT-MICRO catheter in a temperature-controlled mode (3 animals). Clinically, PVI was performed in a homogenous population of 150 consecutive paroxysmal atrial fibrillation patients using CARTO and the QDOT-MICRO catheter in a temperature-controlled mode (75 patients 50 W-ablation index-guided and 75 patients 90 W-4 seconds). Results: Mostly, (94.9%) experimental lesions were transmural in the thin-walled right atrium of swine. However, collateral damage was observed with both catheters in 17.9% of lesions. Clinically, 90 W procedures had a lower first-pass PVI rate (49% versus 81%, P <10 −4 ) and a higher acute PV reconnection rate (21% versus 5%, P =0.004) than 50 W procedures, whereas total procedural duration (62 versus 66 minutes, P =0.09), 1-year sinus rhythm maintenance (88% versus 90%, P =0.6) and safety (1 tamponade per group) were similar in both groups. Conclusions: Experimentally, using the QDOT-MICRO catheter, 90 W-4 seconds lesions are mostly transmural in the thin-walled right atrium of swine (median depth 1.87 mm) with a moderate lesion diameter of 6.62 mm but retain the potential for collateral damage. Clinically, 90 W-4 seconds applications are associated with a lower first-pass PVI rate and a higher acute PV reconnection rate than 50 W applications but similar safety outcomes and effectiveness at 1 year.